Mycorrhizae and a soil ameliorant on improving the characteristics of sandy soil - Herawati, Aktavia; Syamsiyah, Jauhari; Mujiyo, Mujiyo; Rochmadtulloh, Mapan; Susila, Afifah Afiana; Romadhon, Muhammad Rizky (Universitas Sebelas Maret, 2021)
Agricultural constraints on sandy soil are poor chemical characteristics and low biological activity resulting in the soil becoming less productive to be planted. One of the efforts to improve the quality of sandy soil are application of mycorrhizae and a soil ameliorant. The purpose of this study was to determine the effect of mycorrhizae and a soil ameliorant on soil chemical characteristics and soil biological activity. The experiment was arranged using a Complete Randomized Design that had two factors. The first factor (1) was mycorrhizae dose, without mycorrhizae (M0) and six spores of mycorrhizae/plant (M1), and the second factor (2) was types of soil ameliorant, without ameliorant (S0), cow dung (S1), rock phosphate (S2), biochar (S3), cow dung–rock phosphate (S4), cow dung–biochar (S5), and rock phosphate–biochar (S6). The results indicated that combination of six spores mycorrhizae/plant–cow dung 60 tons ha−1–biochar 25 tons ha−1 (M1S5) increased soil organic carbon (SOC) (235%), available P (675%), cation exchange capacity (CEC) (216%), total glomalin (101%), and easily extracted glomalin (69%), decreased exchangeable sodium percentage (66%), and increased absolutely for root infection and spore density than without mycorrhizae and a soil ameliorant (control). The lowest of SOC in non-mycorrhizae and rock phosphate, available P, CEC, root infection, spore density were found on the control, but the lowest of total glomalin and easily extracted glomalin were found on non-mycorrhizae–rock phosphate. The application of mycorrhizae, cow dung, and biochar improved the sandy soil characteristics.